2020
DOI: 10.7554/elife.53889
|View full text |Cite
|
Sign up to set email alerts
|

The E2 Marie Kondo and the CTLH E3 ligase clear deposited RNA binding proteins during the maternal-to-zygotic transition

Abstract: The maternal-to-zygotic transition (MZT) is a conserved step in animal development, where control is passed from the maternal to the zygotic genome. Although the MZT is typically considered from its impact on the transcriptome, we previously found that three maternally deposited Drosophila RNA binding proteins (ME31B, Trailer Hitch [TRAL], and Cup) are also cleared during the MZT by unknown mechanisms. Here, we show that these proteins are degraded by the ubiquitin-proteasome system. Marie Kondo, an E2 conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 50 publications
3
51
1
Order By: Relevance
“…While the role of the GID ligase in the regulation of gluconeogenesis is well-characterized, the conservation of this multiprotein complex throughout eukaryotes suggests that it likely regulates additional pathways. For example, the GID/CTLH complex has a role in erythropoiesis and spermatogenesis in human cells and in embryogenesis in Drosophila ( 62 65 ). Thus, we set out to uncover additional pathways regulated by the GID E3 ligase in yeast by utilizing a combination of mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the role of the GID ligase in the regulation of gluconeogenesis is well-characterized, the conservation of this multiprotein complex throughout eukaryotes suggests that it likely regulates additional pathways. For example, the GID/CTLH complex has a role in erythropoiesis and spermatogenesis in human cells and in embryogenesis in Drosophila ( 62 65 ). Thus, we set out to uncover additional pathways regulated by the GID E3 ligase in yeast by utilizing a combination of mutants.…”
Section: Resultsmentioning
confidence: 99%
“…However, Gid4, while conserved in human cells, is not conserved throughout all eukaryotes. For example, the GID complex in Drosophila lacks an identifiable Gid4 homolog ( 65 ), suggesting an alternate mode of recognition. In addition, in yeast, the protein Gid10 has been identified as an alternate substrate receptor of the GID complex ( 40 , 67 ), although no Gid10-dependent cellular substrates have been identified to date.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological importance of the CTLH E3 is underscored by developmental defects in flies, fish, frogs, and mammals arising from genetic deletions or mutations of its subunits (Han et al, 2016;Javan et al, 2018;Nguyen et al, 2017;Pfirrmann et al, 2015;Soni et al, 2006;Wei et al, 2019;Zavortink et al, 2020;Zhen et al, 2020). Yet, how Gid7 or its human orthologs regulate GID and CTLH E3 ligase complexes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It also remains to be tested whether CG5003 has additional roles later than the observed arrest in the early embryonic divisions, perhaps in maternal proteome clearance after zygotic genome activation. A precedent for this derives from a recent study that identified an E2 and an E3 ligase responsible for the degradation of maternal RNA binding proteins at the maternal-to-zygotic transition (Zavortink et al 2020). Experiments addressing the diversity of E3 ubiquitin complexes and the subsets of targets under their regulation in early embryos should yield new insights into proteome remodeling during embryogenesis.…”
Section: Discussionmentioning
confidence: 99%